Linguocultural Aspect of the Study of Paremiological Units in Linguistics (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article presents the role and linguocultural potential of paremiological units in world linguistics and modern linguistics. The main methods used in the article were direct observation, descriptive-analytical, cultural comparative, contextual and linguistic methods. The article presents general information about the main aspects of paremiological research. The historical and etymological discursive (functional) analysis of the foundations and features of linguoculturology (linguoculturology) and translation studies is shown.The article analyzes the linguocultural toponymic component of proverbs in French and Uzbek. Despite the large number of different toponyms, they are characteristic of different countries, the international component prevails in these proverbs, such proverbs are associated with the universal laws of human thinking, which allows us to find their semantic equivalents in different languages. The relevance of this study lies in the presence of various analyzes of modern proverbs.